SPIRITUALIZING HALAL COSMETIC CONSUMPTION: SUFISM PERSPECTIVE ON MILLENNIAL BUYING BEHAVIOR - Mu'is, Ahmad; Sucipto, Agus; Andriani, Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This paper aims to elaborate the spiritualizing of halal cosmetic buying decision for Islamic millennial. Using descriptive qualitative from many sources in several areas of Indonesia about millennial and halal product decision especially halal cosmetic. After that analytically of that information to give some suggestion. Base on the research found that there are weaknesses in knowledge and religiosity for millennial buyers. They more give attention to fulfill their want and no think the product will give useful for their need and no opposite with the religion. In order to avoid their blind costumer activity so it required classic ascetic religious (sufism approach) to protect. There are takhally, tahalli and tajally in their life. By that way to give them knowledge and well religious for in the future not only to be wise buyers and producers also, they will be creative, innovative, productive, smart and religious.